Clinical researchSelective serotonin reuptake inhibitors for the management of irritable bowel syndrome: A meta-analysis of randomized controlled trials - Rahimi, Roja; Nikfar, Shekoufeh; Abdollahi, Mohammad (Archives of Medical Science, 2008)
Introduction: Selective serotonin reuptake inhibitors (SSRIs) are a class of drugs used for the management of irritable bowel syndrome (IBS) but there is not enough evidence to prove their effectiveness. The aim of the study was to evaluate the efficacy of SSRIs for the management of IBS by meta-analysis technique. Material and methods: PubMed, Embase, Scopus, Web of Science, and Cochrane Central Register of Controlled Trials were searched for studies that investigated efficacy of SSRIs in the management of IBS. Search terms used were “fluoxetine”, “sertraline”, “paroxetine”, “citalopram”, “escitalopram”, or “fluvoxamine” and “irritable bowel”, “functional bowel diseases” or “irritable colon”. Data were searched within the period of 1966 to September 2007. Controlled trials investigating the efficacy of SSRIs in patients with IBS were considered. Results: Five randomized placebo controlled clinical trials met our criteria and were included in the meta-analysis. Pooling of 4 trials for the outcome of improvement in abdominal pain yielded a non-significant odds ratio of 4.68 (95% confidence interval CI of 0.64-34.26, p<0.1268). Pooling 3 studies, from which data for improvement of abdominal bloating were extracted, yielded a non-significant odds ratio of 2.46 (95% CI of 0.4-15.17, p<0.33141). The summary odds ratio for relief of IBS symptoms outcomes among SSRI therapy in 2 trials was 1.31 (95% CI of 0.5-3.39, p<0.5848), a non-significant OR. Conclusions: SSRIs do not significantly improve abdominal pain, abdominal bloating and IBS symptoms. The present results indicate that despite a statistically non-significant effect of SSRIs intake on improving abdominal pain in IBS patients, there is a 5-fold improvement in pain control.